2021
DOI: 10.1186/s12870-021-02921-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transcriptome analysis identifies genes related to fatty acid biosynthesis in the seeds of Prunus pedunculata Pall

Abstract: Background Prunus pedunculata Pall, the deciduous shrub of Amygdalus subgenus in Rosaceae, is a new kind of desert oil-bearing tree. It has a long story of being planted in the West and North of China for sand fixation and desert control. In addition, the seeds of P. pedunculata are rich of oil, especially the monounsaturated fatty acid and polyunsaturated fatty acid. However, little is known about the molecular mechanisms of oil accumulation during the seed development of P. pedunculata. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“… Feng et al (2016) identified 10 KAS genes involved in fatty acid synthesis in eucommia ulmoides seeds by transcriptome sequencing. Bao et al (2021) found that fatty acid biosynthesis related genes LACS6, DGD1 , ACAT1 , AGPAT , WSD1 , EGY2 , and oleosin were highly expressed during late development of Prunus Pedunculata Pall seeds. Xiu et al (2018) found key genes in oil biosynthesis of Paenpnia , containing ACCase , LPCAT , FADs , DGAT.…”
Section: Discussionmentioning
confidence: 95%
“… Feng et al (2016) identified 10 KAS genes involved in fatty acid synthesis in eucommia ulmoides seeds by transcriptome sequencing. Bao et al (2021) found that fatty acid biosynthesis related genes LACS6, DGD1 , ACAT1 , AGPAT , WSD1 , EGY2 , and oleosin were highly expressed during late development of Prunus Pedunculata Pall seeds. Xiu et al (2018) found key genes in oil biosynthesis of Paenpnia , containing ACCase , LPCAT , FADs , DGAT.…”
Section: Discussionmentioning
confidence: 95%
“…Based on three RNA-seq datasets of P. pedunculata deposited in the SRA database ( https://www.ncbi.nlm.nih.gov/sra/ ; accession numbers: SRR13261917, SRR13261918 and SRR13261919) ( Bao et al., 2021 ), we identified the putative RNA editing sites in mitochondrial PCGs. Mapping the RNA-seq data onto the sequences of mitochondrial PCGs by using BWA v0.7.15 ( Li and Durbin, 2010 ) software.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, P. pedunculata was classified as a national near-threatened species by the China Biodiversity Red List – Higher Plants ( Ministry of Ecology and Environment of the People's Republic of China and Science, 2020 ) and been assessed by the IUCN Red List of Threatened Species ( Rhodes and Maxted, 2016 ). Extensive investigations have focused on chloroplast (cp) genome analysis ( Duan et al., 2020 ; Du et al., 2021 ), chemical compounds ( Ma, 2013 ; Lu et al., 2018 ; Yao et al., 2018 ; Li et al., 2020 ), genetic diversity ( Zuo, 2016 ; Bao et al., 2021 ), resistance to various abiotic stress ( Ma, 2006 ; Jiang, 2008 ; Luo, 2009 ; Guo, 2014 ), cultivation technology ( Li, 2017 ; Wang et al., 2020b ; Wang et al., 2021b ), protection and utilization ( Chu et al., 2015 ; Liu, 2017 ; Xiong et al., 2018 ; Bao et al., 2021 ) of P. pedunculata . Previous studies have indicated that P. pedunculata possesses many resistance genes.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al (2016) identified 10 KAS genes involved in fatty acid synthesis in eucommia ulmoides seeds by transcriptome sequencing. Bao et al (2021) found that fatty acid biosynthesis related genes LACS6, DGD1, ACAT1, AGPAT, WSD1, EGY2, and oleosin were highly expressed during late development of Prunus Pedunculata Pall seeds. Xiu et al (2018) found key genes in oil biosynthesis of Paenpnia, containing ACCase, LPCAT, FADs, DGAT.…”
Section: Combined Analysis Of Lipidome and Transcriptomementioning
confidence: 95%